OUTWARD BRAZILIAN FOREIGN DIRECT INVESTMENT: IMPULSES AND RESPONSES - de Oliveira Concer, Ronald; Araujo Turolla, Frederico; Margarido, Mário Antonio (Internext, 2010)
This paper models the outward foreign direct investment from Brazil series using time a series econometrics model, namely the Vector Auto Regressive (VAR) model. We have drawn impulse response functions for the key relevant factors that may explain the outward foreign direct investment flows. We start with a review of the literature on the Dunning location approach to international business. We worked with a data set of quarterly observations from Q1-1995 to Q1-2010. We carried also out Granger causality tests as for determining whether international business travelling should be included as an explanatory variable in our model. Results stressed that although the strong exchange rate in Brazil is often blamed for forcing companies to invest abroad, the evidence found in the aggregate data suggests that there is not a significant relationship between the level of foreign exchange rate and the outward Brazilian foreign direct investment. Differently from previous studies, this paper uses impulse response functions to present dynamic results, thus avoiding the typical binary results “affect” or “don’t affect”, and in so doing we provide a more detailed insight into this important location factor.